Vertebral fracture during one repetition maximum testing in a breast cancer survivor: a case report - Rosenberger, Friederike; Schneider, Justine; Schlueter, Kathrin; Paratte, Jean-Luc; Wiskemann, Joachim (Medicine, 2021)
Rationale: One repetition maximum (1-RM) testing is a standard strength assessment procedure in clinical exercise intervention trials. Because no adverse events (AEs) are published, expert panels usually consider it safe for patient populations. However, we here report a vertebral fracture during 1-RM testing. - Patient concerns: - A 69-year-old breast cancer survivor (body-mass-index 31.6 kg/m2), 3 months after primary therapy, underwent 1-RM testing within an exercise intervention trial. At the leg press, she experienced pain accompanied by a soft crackling. - Diagnosis: - Imaging revealed a partially unstable cover plate compression fracture of the fourth lumbar vertebra (L4) with a vertical fracture line to the base plate, an extended bone marrow edema and a relative stenosis of the spinal canal. - Interventions: - It was treated with an orthosis and vitamin D supplementation. Another imaging to exclude bone metastases revealed previously unknown osteoporosis. - Outcomes: - The patient was symptom-free 6.5 weeks after the event but did not return to exercise. - Conclusion: - This case challenges safety of 1-RM testing in elderly clinical populations. - Lessons: - Pre-exercise osteoporosis risk assessment might help reducing fracture risk. However, changing the standard procedure from 1-RM to multiple repetition maximum (x-RM) testing in studies with elderly or clinical populations would be the safest solution.